Contribution of Neuronal and Glial Two-Pore-Domain Potassium Channels in Health and Neurological Disorders - Yuncheng Luo; Lu Huang; Ping Liao; Ruotian Jiang (Neural Plasticity)
Two-pore-domain potassium (K2P) channels are widespread in the nervous system and play a critical role in maintaining membrane potential in neurons and glia. They have been implicated in many stress-relevant neurological disorders, including pain, sleep disorder, epilepsy, ischemia, and depression. K2P channels give rise to leaky K+ currents, which stabilize cellular membrane potential and regulate cellular excitability. A range of natural and chemical effectors, including temperature, pressure, pH, phospholipids, and intracellular signaling molecules, substantially modulate the activity of K2P channels. In this review, we summarize the contribution of K2P channels to neuronal excitability and to potassium homeostasis in glia. We describe recently discovered functions of K2P channels in glia, such as astrocytic passive conductance and glutamate release, microglial surveillance, and myelin generation by oligodendrocytes. We also discuss the potential role of glial K2P channels in neurological disorders. In the end, we discuss current limitations in K2P channel researches and suggest directions for future studies.